Enhanced ibuprofen removal by heterogeneous-Fenton process over Cu/ZrO2 and Fe/ZrO2 catalysts. Issue 1 (February 2020) - Hussain, Sajid; Aneggi, Eleonora; Briguglio, Sara; Mattiussi, Michele; Gelao, Vito; Cabras, Igino; Zorzenon, Luciano; Trovarelli, Alessandro; Goi, Daniele
Graphical abstract: Highlights: Ibuprofen from liquid waste could be efficiently removed by Fenton-like process Copper supported over zirconia (ZrCu) can almost completely degraded ibuprofen. Copper supported over zirconia promotes a mineralization of about 50 %. Preliminary results suggest ZrCu does not form toxic compounds. ZrCu is a promising catalyst for removal of persistent pollutants from liquid waste Abstract: The aim of this work is to develop new heterogeneous catalysts for the mineralization of Ibuprofen, a pharmaceutical compound commonly found in wastewaters, using a Fenton like process. Copper and Iron catalysts supported over zirconia, eventually doped with strontium were developed. Structural and morphological properties of the materials were investigated by conventional techniques and Fenton-like reactions were carried out in a batch system. Copper/iron-doped zirconia samples exhibited a promising activity in terms of Ibuprofen degradation and mineralization. The best catalyst, copper supported over zirconia, achieved an almost complete degradation of ibuprofen (98 %) with 50 % of mineralization. Optimization of the reaction variables (oxidant dose, pH, catalyst loading and temperature) led to increase process efficiency. Moreover, these catalysts do not produce toxic metabolites which is important when considering the degradation of water pollutants. The present study highlights the potential of copper/iron supported catalysts for the removal of organic compounds in wastewaters via heterogeneous Fenton-like process.